Reducing the gender gap in parental leave through economic incentives? Evidence from the gender equality bonus in Sweden - Olof Rosenqvist (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
Using administrative data from Sweden, I study an internationally unique parental leave policy that rewarded parents with a financial bonus as a function of their division of paid parental leave. Results from a birthdate based regression discontinuity design show that the policy significantly reduced the absolute difference in days of paid leave between the parents. Since parents started earning bonus only after the exhaustion of the 60 reserved days for each parent, the response to the bonus was completely driven by the roughly 55 % of the couples who exhausted all reserved days. Within this group, the effect of the policy was particularly strong in the small group of parents where the father had the highest uptake, causing the effect on the mother-father difference in uptake to be insignificant. Labor market earnings and temporary parental leave (i.e., caring for the child when he/she is too sick to be in school/daycare center), which has been argued to be a good proxy for a parent's general childcare involvement beyond the first years after childbirth, were not significantly affected by the bonus. However, mothers who lowered (increased) their uptake of parental leave in response to the bonus policy displayed negative (positive) point estimates for temporary parental leave and positive (negative) point estimates for labor earnings. While a corresponding pattern for fathers could not be observed, for mothers, the results suggest a potentially important link between the length of the early parental leave and later allocation of time between home and market production.
Keywords: D13; J13; J16; 330; Parental leave; gender equality bonus; home production; regression discontinuity